2020
DOI: 10.3389/fpubh.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Psychological Capital in the Relationship Between Occupational Stress and Fatigue: A Cross-Sectional Study Among 1,104 Chinese Physicians

Abstract: Purpose: This study aimed to explore the association of occupational stress with fatigue and to examine the mediating role of psychological capital (PsyCap) among Chinese physicians. Materials and Methods:A cross-sectional study was conducted in Liaoning province, China, in 2018. Using a multistage stratified sampling method, a total of 1,500 physicians participated and 1,104 (73.6%) physicians responded effectively. The study used a self-administered questionnaire consisting of the 14-item Fatigue Scale (FS-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 62 publications
(72 reference statements)
9
36
1
1
Order By: Relevance
“…Therefore, those reasons might explain the differences. In the current study, there was no gender difference in fatigue, which is consistent with previous literature [38]. However, several previous studies claimed that women were more likely to suffer from fatigue [6,48].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, those reasons might explain the differences. In the current study, there was no gender difference in fatigue, which is consistent with previous literature [38]. However, several previous studies claimed that women were more likely to suffer from fatigue [6,48].…”
Section: Discussionsupporting
confidence: 92%
“…According to the previous literature based on Chinses samples [37], a cut-off ≥7 indicated the caseness of fatigue. The Chinese version of the scale has been widely used in health care settings with good validity and reliability [6,38]. In the study, the Cronbach's Alpha for FS-14 was 0.907.…”
Section: Fatiguementioning
confidence: 89%
See 1 more Smart Citation
“…Fourth, the findings also concert with previous results identifying psychological capital as a critical mediator linking TL and OC. Past studies also stated the mediating role of psychological capital (Carmona-Halty, Schaufeli, & Salanova, 2019;Liao, Hu, Chung, & Chen, 2017;Tian et al, 2020). The results of this study suggest that higher levels of psychological capital facilitate the nurses in attaining their individual as well as organizational goals.…”
supporting
confidence: 62%
“…Considerable studies found the lower prevalence of fatigue ranging from 21.6 to 45.5% [59][60][61][62], whereas Da Silva et al [63] reported the overall incidence rate of fatigue among nursing workers in Brazil was 52%, which is in line with our findings. Moreover, several research observed higher incidence rates of fatigue ranging from 83.7 to 91.9% [54,64,65]. The discrepancy might be attributed to different definitions of fatigue, diverse assessment tools, inconsistent cut-off points and so forth.…”
Section: Discussionmentioning
confidence: 99%